2009
DOI: 10.2337/dc09-0545
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Symptomatic Polyneuropathy With Actovegin in Type 2 Diabetic Patients

Abstract: OBJECTIVETo evaluate the efficacy and safety of actovegin in patients with diabetic polyneuropathy.RESEARCH DESIGN AND METHODSIn this multicenter, randomized, double-blind trial, 567 patients with type 2 diabetes received 20 intravenous infusions of actovegin (2,000 mg/day) (n = 281) or placebo (n = 286) once daily followed by three tablets of actovegin (1,800 mg/day) or placebo three times daily for 140 days. Total symptom score (TSS) of the lower limbs and vibration perception threshold (VPT) were used as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
29

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 20 publications
2
62
0
29
Order By: Relevance
“…Возникновение и течение гнойно-некроти-ческих форм схематически можно представить следующим образом: факторы риска -образова-ние язв -ишемия -гангрена -ампутация [15].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Возникновение и течение гнойно-некроти-ческих форм схематически можно представить следующим образом: факторы риска -образова-ние язв -ишемия -гангрена -ампутация [15].…”
Section: Introductionunclassified
“…В связи с этим разработка новых па-тогенетически обоснованных немедикаментоз-ных методов лечения диабетической стопы, оказывающих непосредственное воздействие на поврежденные ткани и не требующих значи-тельных экономических затрат, является крайне актуальной [7,13,15].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A study of 567 diabetic patients showed no improvement in muscle strength or condition was found after maximal Actovegin infusion for 160 days [11]. Further, Lee et al performed another, more recent blinded, crossover peak aerobic capacity study in healthy human participants [12].…”
Section: Legality and Ergogenic Potentialmentioning
confidence: 99%
“…Также достоверно улучшилась ментальная составляющая качества жизни (p = 0,02). Таким образом, в проведенном исследовании выявле-но положительное влияние препарата Актовегин® как на течение неврологических симптомов (снижение интен-сивности болей, парестезии, онемения), так и неврологи-ческого дефицита (улучшение показателей вибрацион-ной чувствительности и сенсорного компонента ШН-НК) [13]. Учитывая тот факт, что нарушение вибрационной чувствительности является независимым фактором риска развития СДС, данное положительное влияние препарата имеет важное клиническое значение [11].…”
unclassified